Irrigation Water Management Practices that Reduce Water Requirements for Mid‐South Furrow‐Irrigated Soybean. Issue 1 (3rd August 2017) - Bryant, C.J.; Krutz, L.J.; Falconer, L.; Irby, J.T.; Henry, C.G.; Pringle, H.C.; Henry, M.E.; Roach, D.P.; Pickelmann, D.M.; Atwill, R.L.; Wood, C.W.
Abstract : Core Ideas: Irrigation water management practices reduced total water use 21%. Irrigation water management practices increased irrigation water use efficiency 36%. Sensor‐based scheduling reduced irrigation by 50%. Withdrawal for agricultural uses has decreased water levels in the Mississippi Alluvial River Valley aquifer (MARVA), and Mississippi state regulators have responded by requiring withdrawal permits, establishing permitted withdrawal limits, and instituting required minimum levels of irrigation water use efficiency (IWUE) practices. The objective of this research was to determine the effect of integrating irrigation water management (IWM) practices—including computerized hole selection (CHS), surge flow irrigation (SURGE), and sensor‐based irrigation scheduling—on irrigation water use, soybean grain yield, IWUE, and net returns above irrigation costs at the production scale. The experiment was conducted in the Prairie region of Arkansas and the Delta region of Arkansas and Mississippi from 2013 through 2015. The research consisted of 20 paired fields, with the same cultivar, soil type, planting date, and management practices. One field was randomly assigned as the control (conventional, CONV) and the other was instrumented with CHS, SURGE, and soil moisture sensors, that is, IWM. Flowmeters were installed in the inlets to both fields, and the farmers provided yield data. Soybean grain yield averaged 69.0 bu/acre and did not differ between CONV and IWM ( P = 0.6703). Relative to CONV, IWM reduced water use 21% ( P = 0.0198) and increased IWUE 36% ( P = 0.0.0194). Net returns for soybean production above irrigation costs were not different between CONV and IWM, even when pumping depth ranged from 18 ft to 400 ft and diesel costs ranged from $1.60/gal to $3.70/gal ( P ≥ 0.5376). These results demonstrate that implementation of integrated IWM at the production scale reduces the demand on depleted groundwater resources without adversely affecting soybean grain yield or on‐farm profitability.